(untitled) (Brazilian Journal of Health Research, 2023)
Introduction: Antiretroviral therapy (ART) has an impact on improving the life expectancy of people living with HIV (PLHIV), although some factors can make it difficult to continue treatment, such as the complexity of pharmacotherapy, drug interactions, adverse effects, therapeutic failures, and non-adherence. Objective: To gather studies that address pharmaceutical follow-up pharmacotherapeutic services offered to PLHIV to describe the clinical results achieved by offering this service to these patients. Methods: This is an integrative literature review. Literature searches were performed in PubMed and LILACS electronic databases, using the Medical Subject Headings (MeSH) descriptors: “HIV”, “pharmaceutical services”, “medication therapy management”, and “pharmaceutical care”. A total of 354 articles were retrieved, of which nine articles were included because they approached the pharmaceutical clinical service of pharmacotherapeutic follow-up. Results: It was possible to observe that the pharmacists who offered the service promoted better adherence to ART, the identification and resolution of drug-related problems, and carried out health education interventions. Conclusion: There are several pharmaceutical services with the potential to bring clinical benefits to this population, with an emphasis on pharmacotherapeutic follow-up services. However, further studies are still needed to robustly assess the clinical, humanistic and economic impact of these services.